Associations between Responses to the Rhoptry-Associated Membrane Antigen of Plasmodium falciparum and Immunity to Malaria Infection - Topolska, Agnieszka E. (American Society for Microbiology, 2004)
Rhoptry proteins participate in the invasion of red blood cells by merozoites during the malaria parasite's asexual-stage cycle. Interference with the rhoptry protein function has been shown to prevent invasion, and three rhoptry proteins have been suggested as potential components of a vaccine against malaria. Rhoptry-associated membrane antigen (RAMA) is a 170-kDa protein of Plasmodium falciparum which is processed to a 60-kDa mature form in the rhoptries. p60/RAMA is discharged from rhoptries of free merozoites and binds to the red-cell membrane before being internalized to form part of the parasitophorous vacuole of the newly developing ring. We examined the range of anti-RAMA responses in individuals living in an area of endemicity for malaria and determined its association with clinical immunity. RAMA is immunogenic during infections, and at least three epitopes within RAMA are recognized by hyperimmune sera in immunoblots. Sera from individuals living in a region of Vietnam where malaria is endemic possessed strong antibody responses toward two C-terminal regions of RAMA. Cytophilic antibody isotypes (immunoglobulin G1 [IgG1] and IgG3) predominated in humoral responses to both C-terminal epitopes. Acute episodes of P. falciparum infection result in significant boosting of levels of antibody to an epitope at the extreme C terminus of RAMA that harbors the red-cell-binding domain. Immunity to P. falciparum infection was linked to elevated levels of IgG3 responses to this functional domain of RAMA, suggesting that the region may contain a protective epitope useful for inclusion in a multiepitope vaccine against malaria.